Gilbert as Disrupter: Modes (of Many Sorts) in the Theory of Argument - Groarke, Leo (Informal Logic, 2022)
Michael Gilbert’s multi-modal theory of argument challenges earlier accounts of arguing assumed in formal and informal logic. His account of emotional, visceral, and kisceral modes of arguing rejects the assumption that all arguments must be treated as instances of one “logical mode.” This paper compares his alternative modes to other modes proposed by those who have argued for visual, auditory, and other “multimodal” modes of arguing. I conclude that multi-modal and multimodal (without the hyphen) modes are complementary. Collectively, they represent an important attempt to radically expand the scope of informal logic and the argumentation that it studies.